INTRODUCTION OF VIRTUAL REALITY SYSTEMS IN THE TRAINING OF SPORTS COACHES - Fomenko , Olena; Sorochinska , Marina (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
Reforming education in Ukraine promotes the use of innovative technologies in physical education and sports, which is one of the promising areas of education development. For modern society, the introduction of innovative technologies in education has not so much theoretical as pragmatic significance, since in the conditions of globalization it concerns its historical development and prospects, which are associated with the so-called «high technologies». The paper considers the possibility of using virtual reality technologies in physical education and sports during the training of athletes.